Knowledge and Colonialism: Eighteenth-century Travellers in South Africa - Huigen, Siegfried (Atlantic World, 2009)
Knowledge and Colonialism examines writings and drawings of eighteenth-century scientific travellers in South Africa against the background of administrative and commercial discourses. It is argued that these travellers benefited more from their relationship with the colonial order than the other way around.